2021
DOI: 10.18280/rcma.310206
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Additive Manufacturing in Aerospace Application

Abstract: In the era of Digital Manufacturing and supporting state-of-the-art, i.e. Additive manufacturing (AM) technology is getting more popular known as 3D printing, AM has created its own space in the fastest growing industry. 3D printing has evolved in previous years, and now, it is being used in several social life domains. The main application of this process has found in prototyping, aerospace industry, biomedical and dental implants. Additive manufacturing prints a part in a layer by layer or line by line patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The applicability of 3D printing in a large amount of research fields has improved the knowledge of these technologies in different subjects. [1][2][3][4] In the literature, many research papers related to the characteristics of 3D printing materials for the industry field can be easily found. [5][6][7][8] The 3D fabrication technologies are divided into two great groups depending on the creation process.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of 3D printing in a large amount of research fields has improved the knowledge of these technologies in different subjects. [1][2][3][4] In the literature, many research papers related to the characteristics of 3D printing materials for the industry field can be easily found. [5][6][7][8] The 3D fabrication technologies are divided into two great groups depending on the creation process.…”
Section: Introductionmentioning
confidence: 99%
“…Other interesting materials include carbon-fiber molds or alumina-ceramic models, which can be produced in a very short time, usually around 7 days, with very good aesthetic results ( 71 ). In particular, long-term results related to this new generation of materials showed that they remained very stable, even years after implantation ( 71 , 72 ). For both the approaches, regarding the use of new materials and standards, a higher complication rate has been reported in patients with severe co-morbidities and older age ( 71 – 73 ).…”
Section: Surgical Techniques and Prosthesismentioning
confidence: 99%
“…It is claimed that this item is up to 25% lighter and more complicated than its counterparts, and that it combines numerous previously assembled parts of a single piece. 3D printing is used by Meena Pant et al 9 to make Aircraft engine components. Bombardier, the largest global aircraft manufacturer, has received Pratt & Whitney's first engine for the C-Series passenger aircraft.…”
Section: Importance Of Am In Aerospace Applicationmentioning
confidence: 99%